2006
DOI: 10.1158/0008-5472.can-05-1578
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin-Cytosine Deaminase Fusion Protein Suppresses Tumor Growth by Targeting Neovascular Endothelial Cells

Abstract: Endostatin, an angiogenesis inhibitor tested in multiple clinical trials, selectively targets neovascular endothelial cells, suppressing tumor growth. To enhance the therapeutic efficacy of endostatin, we fused endostatin with cytosine deaminase, which converts a prodrug 5-flucytosine into a cytotoxic 5-fluorouracil. This therapeutic strategy was developed based on the observation that the endostatin-green fluorescence protein gene and endostatin-luciferase gene selectively target to endothelial cells in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…In vitro tube formation assay To evaluate the antiangiogenic activity of PEDF produced by hMSCs-PEDF, an in vitro tube formation assay was performed as described previously (Ou-Yang et al, 2006). Matrigel (50 ml; BD Biosciences, San Jose, CA, USA) was added to each well of a 96-well plate and allowed to polymerize.…”
Section: Western Blotmentioning
confidence: 99%
“…In vitro tube formation assay To evaluate the antiangiogenic activity of PEDF produced by hMSCs-PEDF, an in vitro tube formation assay was performed as described previously (Ou-Yang et al, 2006). Matrigel (50 ml; BD Biosciences, San Jose, CA, USA) was added to each well of a 96-well plate and allowed to polymerize.…”
Section: Western Blotmentioning
confidence: 99%
“…Tube formation assay was done as previously described (2). In brief, 3 × 10 4 endothelial cells were seeded on a layer of polymerized Matrigel (BD Biosciences) in a 96-well plate.…”
Section: Translational Relevancementioning
confidence: 99%
“…Apart from angiogenesis inhibitors, so-called vascular disrupting agents targeted at the established tumor vasculature are currently being investigated in clinical trial. Recently, we revealed that an endostatin-cytosine deaminase fusion protein possesses the tumor vessel-targeting property of endostatin to allow selective tumor-killing effect of cytosine deaminase, producing potent antitumor activity (2).…”
mentioning
confidence: 99%
“…The EZC-prostate model in which prostate cancer cell lines (LNCaP-Luc and PC-3-Luc) stably expressing firefly luciferase enzyme facilitated live imaging of established orthotopic prostate cancer xenografts (25, 29) and enabled real-time monitoring of prostate tumor growth and metastases without having to sacrifice the animals. An orthotopic model by injecting tumor cells into the prostate better mimics the prostate cancer in clinics than a subcutaneous model.…”
Section: Discussionmentioning
confidence: 99%